'Colonial livery' and the chemise à la reine, 1779–1784. (September 2018) - Ashelford, Jane
Abstract : When Jane Austen wrote in January 1801 that 'Mrs Powlett was at once expensively and nakedly dressed', the fashion for muslin dresses had existed for some eighteen years. This article examines the crucial period between 1779 and 1784 when the muslin garment, which became known as the chemise à la reine, was developed and refined. Originating in the French West Indies, the gaulle was the 'colonial livery' worn by the wives of the white elite, the 'grands blancs', and first appeared as a costume in a ballet performed in Paris in 1779. The version worn by Queen Marie Antoinette in Vigée Le Brun's controversial portrait of 1783 provoked, according to the Baron de Frénilly, 'a revolution in dress' which eventually destabilized society. The article focuses on the role played by Saint-Domingue, France's most valuable overseas possession, in the transference of the gaulle from colonial to metropolitan fashion, and how the colony became one of the major providers of unprocessed cotton to the French cotton industry.